Globus pallidus internus deep brain stimulation for dystonic conditions: a prospective audit. - Yianni, J; Bain, P; Giladi, N; Auca, M; Gregory, R; Joint, C; Nandi, D; Stein, J; Scott, R; Aziz, T (2003)
In the current era of functional surgery for movement disorders, deep brain stimulation (DBS) of the globus pallidus internus (GPi) is emerging as the favoured target in the treatment of patients with dystonia. The results of 25 consecutive patients with medically intractable dystonia (12 with generalised dystonia, 7 with spasmodic torticollis, and 6 with other types of dystonia) treated with GPi stimulation are reported. Although comparisons were limited by differences in their respective neurological rating scales, chronic DBS benefited all groups, resulting in clear and progressive improvements in their condition. This study clearly demonstrates that DBS of the GPi provides amelioration of intractable dystonia.